IMPLEMENTATIONHIV -AIDS PREVENTION AND TRETMENT PROGRAM IN SOUTH SUMATERA, INDONESIA - Najmah, Asmaripa Ainy; Sunarsih, Elvi; Boursnell, Melanie (ARCHIVE OF COMMUNITY HEALTH, 2013)
Human immunodeficiency virus (HIV) and Acquired Immune Deficiency Syndrome(AIDS) are worldwide public health issues. The spread of HIV-AIDS in high-risk groupshas been very rapid. This paper reports on a small-scale project which investigated attitudes to prevent ion and treatment programs for HIV-AIDS in Indonesia. This is important as there is a dearth of information about the number, type and spread of programs inthe region. Whilst it is known that programs have been implemented in various healthsectors HIV-AIDS rates continue to increase in this area. This is adescriptive study gatheringexploratory information about the number and nature of implementation of programs for theprevention and treatment of HIV-AIDS in the South Sumatra province. The data consists ofqualitative interviews with six key informants and secondary health data from these agencies.Results indicate that more cases were found between 2005 and 2011 in Palembang city, SouthSumatera.The increase of cases was supported by many health resources and services of HIV-AIDSprevention and treatment programs Furthermore, more HIV-AIDS cases are detected when theagencies are able to gain adequate funding and also have opportunities to engage incollaborativeworking practices. Barriers apparent in this study to reducing the spread of HIV-AIDS in thisarea appear to be related to lack of funding and limited prevention programs.
Keywords: HIV-AIDS, evaluation, prevention, treatment, public health